Tratamento de efluentes: um estudo sobre a viabilidade de utilização de coagulantes naturais em laticínios no município de Ituiutaba-MG - Souza, Junélia Alves de (2022)
The treatment of effluents allows the reuse of water that goes through procedures has been carried out currently with the application of chemicals. Still, through several researches this scenario has been changing with the emergence of natural coagulants on the market, offering a healthier environment. This study aimed to analyze the feasibility of introducing organic coagulants in effluent treatment systems in dairy with high polluting potential in the city of Ituiutaba-MG. For this purpose, the raw effluent was initially collected, followed by pre-treatment in the laboratory. After these steps, comparative analyzes were performed using tanfloc SG and aluminum sulfate. The experiments were carried out in partnership with the laboratory of the Instituto Federal do Triângulo Mineiro - Campus Ituiutaba, using the jar test at 130 rpm for 1 minute, 30 rpm for 15 minutes and 20 minutes at rest. for sedimentation. For each liter of wastewater treated in a jar test, 0.6 mL of tanfloc and 0.04g of aluminum sulfate were used for the analysis of BOD (Biochemical Oxygen Demand), COD (Chemical Oxygen Demand), sedimentable materials, oils and greases, total suspended solids, surface-active substances, according to CONAMA Resolution No. 430, of May 13, 2011. As a result, it was observed that in the effluent treated with aluminum sulfate the reductions were: BOD = 18 .8%, COD = 16.8%, sedimentable materials = 100%, oils and greases = 8.1%, suspended solids = 5.7% and surface-active substances = 3.7%. While when the same effluent was treated with the natural coagulant Tanfloc, the reductions were: BOD = 17.4%, COD = 21.5%, sedimentable materials = 100%, oils and greases = 81%, suspended solids = 75.9 % and surface-active substances = 70.7%. In short, the natural coagulant proved to be efficient when compared to a coagulant commonly used in the dairy industries, aluminum sulfate, which indicates the feasibility of using it for the treatment of these effluents.